OS02.4.A Molecular characterization of adult cerebellar glioblastomas identifies distinct prognosis subgroups. (9th September 2021) - Picart, T; Poncet, D; Barritault, M; Pallud, J; Metellus, P; Zouaoui, S; Bauchet, L; Guyotat, J; Gabut, M; Honnorat, J; Ducray, F; Meyronet, D
Abstract: BACKGROUND: Adult cerebellar glioblastomas (cGBM) are very rare and recent studies have shown that they constitute a heterogeneous group of gliomas. The aim of the present study was to characterize the prevalence and prognostic significance of major driver molecular alterations in a large series of cGBM. MATERIAL AND METHODS: Adults with histologically proven cGBM diagnosed between 2003 and 2017 were identified from the French brain tumor database and the Club de Neuro-Oncologie of the Société Française de Neurochirurgie. Tumors were reviewed and reclassified according to WHO 2016. Targeted sequencing was performed, including determination of H3F3A, TERTp, IDH1/2, FGFR1, BRAF and EGFR status. RESULTS: A total of 83 adult patients (median age 57 years) with cGBM (hemispheric n= 47, vermian n=14 or both n=22) were identified. Median overall survival was 10 months. Main molecular alterations observed were TERT promoter, H3F3A K27M, hotspot FGFR1 (N546 and K656), BRAF mutations, EGFR amplification and ATRX loss of expression in 19.2%, 18.8%, 10.9%, 2.6%, 19.5% and 22.7% of patients, respectively. cGBM could be classified into 6 mutually exclusive subgroups associated with age at diagnosis and prognosis: pTERT and/or EGFR amplified tumors (n=22, 26.5%, median age = 62 years, median OS = 4 months), H3K27M-mutant tumors (n=15, 18.1%, median age = 48 years, median OS =8 months), tumors with MAPK pathway activating mutations (FGFR1, BRAF) or occurring in NF1 patients (n=15, 18.1%, median age = 41 years, median OS = 57 months), radiation-induced tumors (n=5, 6%, median age = 47 years, median OS = 5 months), IDH-mutant tumors (n=1) and unclassified tumors (n=25, 30.1%, median age = 63 years, median OS = 17 months). In multivariate analysis, MAPK activating mutations and ATRX loss of expression were independently associated with a better outcome and pTERT/EGFR alterations with a worse outcome. CONCLUSION: About 18% of tumors diagnosed as cGBM harbor actionable MAPK activating genetic alterations. Targeted sequencing enables to classify these tumors into clinically relevant subgroups.